2002
DOI: 10.1051/lait:2002038
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved air effects on lactose isomerisation and furosine formation during heat treatment of milk

Abstract: -The influence of dissolved air on lactose isomerisation and the Maillard reaction during heat treatment of milk was investigated, lactulose and furosine being the chemical parameters studied, respectively. For all treatments, the lowest contents of lactulose were found in samples bubbled with air, probably due to oxidative degradations during the heating of the milk. A lower formation of furosine was also detected in samples with air than in samples subjected to a previous de-aeration step. In the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In addition, Aminoreductone (AR) is one of the products of the Maillard reaction. The decrease in DO content in raw milk before heating will inhibit the oxidative degradation of AR during the heating process to maintain a high AR concentration after heating, which is beneficial to maintaining the quality of commercial milk [ 8 ]. In terms of color, the DO level also plays a role in milk.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Aminoreductone (AR) is one of the products of the Maillard reaction. The decrease in DO content in raw milk before heating will inhibit the oxidative degradation of AR during the heating process to maintain a high AR concentration after heating, which is beneficial to maintaining the quality of commercial milk [ 8 ]. In terms of color, the DO level also plays a role in milk.…”
Section: Introductionmentioning
confidence: 99%
“…The accelerate effect of oxygen on the rate of browning may be attributed to the fact that oxygen is required for formation of some interme- Although no data are reported on the influence of oxygen on the Maillard reactions in glucose syrup, some authors have studied the effects of oxygen on this reaction. Rada-Mendoza, Villamiel, and Olano (2002) demonstrated that the dissolved oxygen has a significant effect on the formation of Amadori compounds during the heat treatment of milk. Hayase, Shibuya, Sato, and Yamamoto (1996) observed less browning under aerobic conditions.…”
Section: Resultsmentioning
confidence: 99%